1994
DOI: 10.1002/aoc.590080407
|View full text |Cite
|
Sign up to set email alerts
|

Biomethylation and biotransformation of arsenic in a freshwater food chain: Green alga (chlorella vulgaris)→shrimp (neocaridina denticulata)→killifish (oryzias iatipes)

Abstract: Tolerance, bioaccumulation, biotransformation and excretion of arsenic compounds by the freshwater shrimp (Neocaridina denticulata) and the killifish (Oryzius latipes) (collected from the natural environment) were investigated. Tolerances (LC,,) of the shrimp against disodium arsenate [abbreviated as As(V)], methylarsonic acid (MAA), dimethylarsinic acid (DMAA), and arsenobetaine (AB) were 1.5, 10, 40, and 15Opg As ml-I, respectively. N . denticulata accumulated arsenic from an aqueous phase containing 1 pg As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 20 publications
2
31
1
Order By: Relevance
“…These results are consistent with previous studies that have also documented a biodiminution of As in aquatic food webs [Maeda, 1994;Chen and Folt, 2000]. This may be the result of relatively high levels of As excretion relative to assimilation in freshwater organisms [Maeda et al, 1992;Kuroiwa et al, 1994;Suhendrayatna et al, 2002]. Arsenic concentrations in zooplankton and in fish across sites also decreased with increasing 13 C suggesting that more pelagic pathways of carbon resulted in higher As bioaccumulation in biota [France, 1995].…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous studies that have also documented a biodiminution of As in aquatic food webs [Maeda, 1994;Chen and Folt, 2000]. This may be the result of relatively high levels of As excretion relative to assimilation in freshwater organisms [Maeda et al, 1992;Kuroiwa et al, 1994;Suhendrayatna et al, 2002]. Arsenic concentrations in zooplankton and in fish across sites also decreased with increasing 13 C suggesting that more pelagic pathways of carbon resulted in higher As bioaccumulation in biota [France, 1995].…”
Section: Discussionsupporting
confidence: 91%
“…However, the fate of arsenic in terrestrial ecosystems is still largely unknown. Except for some studies on arsenic species in freshwater food chains, 1,2 freshwater algae, 3 and fish, 4 only a few papers have been published about arsenic species in terrestrial plants such as vegetables, 5 moulds 6 and mushrooms. 7,8 Arsenobetaine and arsenocholine have been identified in the terrestrial environment thus far only in mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings point to the role of S-adenosylmethionine, or a related sulfonium compound as possible methyl donors. Arsenic biomethylation and biotransformation has also been demonstrated in a freshwater environment (Kuroiwa et al, 1994). Byrne et al (1995), in a study of arsenic-accumulating mycorrhizal and saprophytic mushrooms, identified and confirmed the presence of methylarsonic acid, arsenite, arsenate, dimethylarsinic acid and arsenobetaine.…”
Section: Arsenicmentioning
confidence: 90%